Azospirillum argentinense REC3 and its glycosylated flagellin AzFlap reduce lesions caused by Botrytis cinerea on strawberry leaves = Azospirillum argentinense REC3 y su flagelina AzFlap glicosilada reducen las lesiones causadas por Botrytis cinerea en hojas de frutilla - Correa Deza, Maria Alejandra (2026)
Among the pathogenic fungi of strawberry (Fragaria ananassa Duch.), Botrytis cinerea, a filamentous necrotrophic fungus that causes gray mold, stands out worldwide for its ubiquity and prevalence. Chemical control has been the most effective method used for years to manage B. cinerea in strawberry crops. However, the frequent use of numerous fungicides has increased issues related to pathogen resistance, resurgence, and toxic residues. In this study, we propose the use of the plant growth-promoting bacterium Azospirillum argentinense REC3 and its flagellin AzFlap, whether non-glycosylated or glycosylated, for the control of B. cinerea. We observed that only REC3 inhibited the mycelial growth of B. cinerea in vitro, whereas AzFlap had no inhibitory effect. Moreover, REC3 and only its glycosylated flagellin AzFlap contributed to reducing lesions caused by B. cinerea on detached strawberry leaves.